Pengaruh Model Pembelajaran STAD (Student Team Achievement Divisions) terhadap Kemampuan Manganalisis Struktur Teks Eksplanasi Siswa Kelas XI SMA Negeri 2 Lubuklinggau - Febriani, Wuri Intan; Effendi, M. Syahrun (UNIB Press, 2021)
The purpose of this study was to determine the effect of the STAD (Student Team Achievement Divisions) learning model on the ability to analyze the explanatory text structure of class XI students of SMA Negeri 2 Lubuklinggau. The research method used a pure experimental method with a pre-test-post-test control group research design. The population of this study was 198 high school class XI students consisting of 6 classes. The sampling technique used Cluster Random Sampling technique and the research sample was class XI IPA 1 totaling 33 as the experimental class and class XI IPA 3 with 35 as the control class. Data collection using test techniques and analyzed using the